Pengujian Pecking Order Theory dan Static Trade Off Theory pada Perusahaan Go Public di BEJ - Joko, Fx Agus (Jurnal Widya Manajemen & Akuntansi, 2005)
This research will briefly test whether financing decision of go public companies in, Jakarta Stock Exchange based on pecking order theory or static trade off theory. The source of data are from financial report of 158 manufacture companies in Jakarta Stock Exchange from 1998 to 2002.